Aplikasi Microsoft Project Untuk Analisa Kinerja Waktu Dengan Metode Precedence Diagram Method - Rosmiyati Yusup; Arfan Utiarahman; Apriyanto Pahrun (Transbahasa, 2025)
The problem of delays in construction project is a significant challenge because it can impact the timeliness of completion costs, and the quality of the final results. This study aimed to identify the critical activities in the maritime laboratory building construction project and analyze time performance using Microsoft Project software through the Precedence Diagram Method (PDM). The research was conducted using a case study approach based on project data to determine the critical trajectory and analyze time performance. Based on the analysis, the project has 32 critical activities, all of which have a total float of 0, indicating that there should be no delays whatsover. Projects that were originally scheduled for 8 months can be shortened to 7 months through scheduling optimization with the PDM method. Microsoft Project can identify critical activities, provide start and end time information (ES, EF, LS, LF), and support decision-making in time management. Thus, the application of the Microsoft Project-based PDM method has proven to be effective in increasing the efficiency of the completion time of maratime laboratory construction projects.